Cloning and nucleotide sequence of the Myxococcus xanthus lon gene: indispensability of lon for vegetative growth. - Tojo, N (1993)
The lon gene of Escherichia coli is known to encode protease La, an ATP-dependent protease associated with cellular protein degradation. A lon gene homolog from Myxococcus xanthus, a soil bacterium which differentiates to form fruiting bodies upon nutrient starvation, was cloned and characterized by use of the lon gene of E. coli as a probe. The nucleotide sequence of the M. xanthus lon gene was determined. It contains an open reading frame that encodes a 92-kDa protein consisting of 817 amino acid residues. The deduced amino acid sequence of the M. xanthus lon gene product showed 60 and 56% identity with those of the E. coli and Bacillus brevis lon gene products, respectively. Analysis of an M. xanthus strain carrying a lon-lacZ operon fusion suggested that the lon gene is similarly expressed during vegetative growth and development in M. xanthus. In contrast to that of E. coli, the M. xanthus lon gene was shown to be essential for cell growth, since a null mutant could not be isolated.